Partisipan Masyarakat Dalam Pengelolaan Jalan: Keterkaitan Teori Partisipan Dengan Siklus Pembangunan - IGW. Samsi Gunarta; Tasripin Sartijono; Yogi Nugraha; Yeti Nuryati (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
The gap in capacity of the local government in managing the village roads is somehow filled by efforts of the community to develop and construct their own road. This is a strong indicator that community participation can conctribute directly in regional economy development in particular to improve accessibilty and mobility. However such efforts seem likely to be more output oriented than outcome based oriented. In addition, these are unlikely to be sustainable. A research funded by the Directorate General of Municipality and Rural Development (TPTP), Ministry of Settlement and Regional Infrastructure (MSRI) is designated to look at this matter and seeks for the best practice in managing partnership between community and govermment in road management. The study took 4 cases of village road management involving community participantion in District of Bandung, Bandung Municipality, District of Kuningan, and District of Ciamis, West Java. The qualitative assessment on these showed that the disorientations and sustainability issue are generated by the failure in integrating the public participation principles within the project cycle. The weaknesses in associated with planning, design, and evaluation is required significant improvment. To improve this situation, technical advisory form local government is suggested. In addition to this, the study has also suggested the use of standard references in assessing the performance of community participation of a road project. This would function as a guide in community based road management. Two papers regarding this subject would be published in two series of this journal. The first discusses the basic principles and process of community participation in road project, wile the next one would provide information of assessment results for the 4 study cases area in Bandung, Kuningan, and Ciamis